PENGEMBANGAN PERANGKAT PEMBELAJARAN BERDASARKAN PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMP NEGERI 1 GUNUNG MALELA - Christa Voni Roulina Sinaga (Universitas Islam Sumatera Utara, 2018)
Abstract. The aims of this research is: (1) describe the level of mastery learning and increasing students’ mathematical communication ability with problem-based learning, (2) describe students’ activity during the learing process with problem-based learning, and (3) describe students’ response to the component during problem-based learning. This research is development research. The population of this research are all of students in SMP N 1 Gunung Malela, and the sample chosen is random with VII-3 and VII-4 with 32 students for each class. The instrument used consisted of a test mathematical communication ability of student in description form. The instrumen has been declared eligible validation and had coefisien reability pre-tes and pos-tes 0,81 and 0,62. The results of this research shown that: (1) the level of students’ mastery learning mathematical communication ability in the classical is 87,50% while the increasing of students’ mathematiucal communication abilityin first trial 2,73 increase to 3,05 in the second trial. The most increasing aspect from mathematical communication ability is drawing, (2) students’ activity during learing process with problem based learning has on efektive criteria, and (3) students’ response to the component during problem-based learning has a positive respons. The research suggests to use problem based learning as the alternative way for teacher to increase students mathematical communication abilities. Keywords: Problem Based Learning, and Mathematical Communication Ability